Observation of nine previously reported and 10 non-reported SLC4A11 mutations among 20 Iranian CHED probands and identification of an MPDZ mutation as possible cause of CHED and FECD in one family. Issue 11 (16th August 2019) - Moazzeni, Hamidreza; Javadi, Mohammad Ali; Asgari, Danial; Khani, Marzieh; Emami, Mohammad; Moghadam, Abolfazl; Panahi-Bazaz, Mahmoud-Reza; Hosseini Tehrani, Mehdi; Karimian, Farid; Hosseini, Bagher; Nekuie Moghadam, Tayebeh; Hassanpour, Hossein; et al.
Abstract : Background/aims: SLC4A11 is the only known causative gene of congenital hereditary endothelial dystrophy (CHED). Mutation screenings have shown that most but not all patients with CHED harbour mutations in SLC4A11, suggesting that other CHED-causing genes may exist. We aimed to screen SLC4A11 in Iranian patients to learn the mutation spectrum of this gene among Iranians and to gain further knowledge on potential contribution of other genes to CHED aetiology. Methods: SLC4A11 was screened in 21 Iranian patients with CHED by sequencing. Previously unreported variations were checked in at least 200 controls, and segregation analysis within families and bioinformatics predictions on effects of variations were performed. Exome sequencing was done for the single patient without an SLC4A11 mutation and for her parents. Results: Nine previously reported and 10 unreported SLC4A11 mutations were observed among 20 patients; a mutation was not found in one patient. A mutation in MPDZ was identified as the only candidate cause of CHED in this patient. Her mother who carried the same mutation was diagnosed with Fuchs endothelial corneal dystrophy (FECD). Conclusion: SLC4A11 mutations are the usual cause of CHED in Iranians. The 10 novel mutations observed contribute significantly to the approximately 85 mutations reported since discovery of the role of the gene in CHED pathogenesis more than 10 years ago. MPDZ mutations may be a cause of CHED and even FECD in a minority of patients. Proposed functions of MPDZ with respect to tight junctions and maintenance of the corneal endothelial barrier are in accordance with a role in corneal endothelial pathobiology.